Formation of Public Opinion on the 10% Ethanol Fuel Issue: A Framing Analysis of the TikTok Account of Liputan6 and SCTV - Rezza Maolya Setya Pratiwi; Nadia Itona Siregar (Universitas Negeri Yogyakarta, 2025)
The policy of blending fuel with 10% ethanol is a government policy program implemented through the Ministry of Energy and Mineral Resources (ESDM). The E10 program aims to reduce carbon emissions, decrease fuel imports, and support the transition to renewable energy. However, the media has shaped this policy issue in a way that creates public opinion through the framing conducted by Liputan6 and SCTV. As a result, the public opinions that emerged were both supportive and opposing. This study aims to analyze the framing of news coverage regarding 10% ethanol fuel (E10) on the TikTok account of Liputan6 SCTV and to examine the formation of public opinion that emerged from it. The research employs a descriptive qualitative method using Robert Entman’s framing analysis through four elements: define problems, diagnose causes, make moral judgement, and treatment recommendation. Primary data were obtained from four TikTok video contents by Liputan6 SCTV related to the E10 policy during the October 2025 period. Meanwhile, secondary data were collected from books, journals, and websites relevant to this topic. The results of the study indicate that the media framed the E10 policy as a government effort to create alternative energy, reduce fuel imports, and support environmentally friendly energy. However, the media also highlighted the risks of ethanol use for vehicles, which led to public opinion that tended to be skeptical and opposed to the policy. This study demonstrates that public agenda and media framing have a significant influence in shaping public perceptions of the 10% bioethanol policy in Indonesia.